Experimental study on inhibition of spontaneous combustion of different-rank coals by high-performance m-Cresol water-based inhibitor solutions. (15th December 2022) - Lu, Wei; Gao, Ao; Sun, Weili; Liang, Yuntao; He, Zhenglong; Li, Jinliang; Sun, Yong; Song, Shuanglin; Meng, Shaocong; Cao, Yingjiazi
Abstract: A kind of simple and efficient m-Cresol water-based inhibitor was proposed. The inhibitory effects of its solutions on the spontaneous combustion of different-rank coals were discussed. Furthermore, the micromorphology and wetting characteristics of different-rank coals were analyzed through a scanning electron microscope and a contact angle meter, respectively. Besides, the weight loss rates, oxidation characteristics, pore structure characteristics and free radical changes of different coal samples were investigated by a thermogravimetric analyzer, temperature-programmed experiments, a surface area analyzer and an electron spin resonance spectrometer, respectively. The results indicate that the prepared inhibitor solution at the 0.3 wt% sodium dodecyl sulfate (SDS) not only boasts good emulsification and wetting performance, but also plays a role in permeability enhancement. The m-Cresol/SDS solution can wet the coal surface and permeate the inner pore surface, forming a uniform inhibitor layer on both the coal surface and the inner pore surface to isolate oxygen, retain water and inhibit free radical generation. Moreover, it can not only effectively reduce the weight loss rate, CO production, specific surface areas and free radical concentration in the oxidation process of CoalXLH, CoalBLT and CoalYQ, but also improve the inhibition rate (to 79.1%, 67.4% and 54.3% at 170 °C respectively). Highlights: 0.3 wt% SDS has good ability of emulsification, wetting and permeability. Physicochemical characteristics of inhibited coal samples were studied. The m-Cresol/SDS inhibitor solution has excellent inhibition effects. Physical-chemical inhibition mechanism of the m-Cresol/SDS solution is proposed.